Comparative Study of Bill of Quantity Planning and Actual Work Mechanical, Electrical and Plumbing Construction of Hospital Buildings - Darmawan Pontan; Dieta S K; Abizar M; Andi T P; Daffa M B; Fajar W (International Journal of Social Service and Research, 2023)
One important aspect in the planning process of a project is the calculation of the volume of work or commonly known as the Bill of Quantity (BoQ). BoQ itself is a document detailing the type of work, volume and unit of measurement of all work items to be carried out to determine the final estimated value of a construction job. Calculation of the volume of work will be carried out based on the Work Plan and Conditions (RKS) and drawings that have been approved by the owner. In the construction industry, MEP or Mechanical, Electrical, and Plumbing is an important factor to realize a building or buildings whose installation system is safe and of good quality. MEP itself is the expertise to plan, design, and manage mechanical, electrical, and piping systems in a building. The actual BoQ results were 5.74% greater than the planned BoQ caused by changes in the work of installing the plumbing system. As well as the most influential factors were changes in design drawings that did not match the conditions in the field and incomplete design drawings.